2017
DOI: 10.4314/gjds.v14i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Adaptive Capacity to Climate Change among Smallholder Rural Households in the Bongo District, Ghana

Abstract: This study examined

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Majority of the research works on determinant factors of CCA used quantitative, qualitative or mixed-methods analysis. Majority of the studies in pastoral (Chingala et al, 2017;Mengistu and Haji, 2015;Tilahun et al, 2017;Zampaligré et al, 2014), agro-pastoral (Balama et al, 2013;Bryan et al, 2013;Kgosikoma et al, 2018;Kima et al, 2015; Mengistu and Haji, 2015;Serkalem et al, 2014;Zampaligré et al, 2014;Silvestri et al, 2012) and smallholder farmers (Ajao et al, 2011;Alemayehu and Bewket, 2017;Belay et al, 2017;Comoé and Siegrist, 2015;De Jal on et al, 2015;Gedefaw et al, 2018;Legesse et al, 2013;Mabe et al, 2014;Misganaw et al, 2014;Mudombi-Rusinamhodzi et al, 2012;Nabikolo et al, 2012;Osumanu et al, 2017;Ozor et al, 2010;Yila and Resurreccion, 2013) used logistic/logit regression models (binary/ordered/multinomial) to evaluate the determinant factors of CCA. This highlights that the various kinds of logistic regression models are widely implemented in assessing the determinant factors of CCA research studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of the research works on determinant factors of CCA used quantitative, qualitative or mixed-methods analysis. Majority of the studies in pastoral (Chingala et al, 2017;Mengistu and Haji, 2015;Tilahun et al, 2017;Zampaligré et al, 2014), agro-pastoral (Balama et al, 2013;Bryan et al, 2013;Kgosikoma et al, 2018;Kima et al, 2015; Mengistu and Haji, 2015;Serkalem et al, 2014;Zampaligré et al, 2014;Silvestri et al, 2012) and smallholder farmers (Ajao et al, 2011;Alemayehu and Bewket, 2017;Belay et al, 2017;Comoé and Siegrist, 2015;De Jal on et al, 2015;Gedefaw et al, 2018;Legesse et al, 2013;Mabe et al, 2014;Misganaw et al, 2014;Mudombi-Rusinamhodzi et al, 2012;Nabikolo et al, 2012;Osumanu et al, 2017;Ozor et al, 2010;Yila and Resurreccion, 2013) used logistic/logit regression models (binary/ordered/multinomial) to evaluate the determinant factors of CCA. This highlights that the various kinds of logistic regression models are widely implemented in assessing the determinant factors of CCA research studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several research works have been conducted in different corners of SSA on the perception of farmers to climate change adaptation (CCA) and the socioeconomic factors that influence the adaptation of these farmers to the changing climate (Mudombi-Rusinamhodzi et al, 2012;Muller and Shackleton, 2014;Nabikolo et al, 2012;Osumanu et al, 2017;Ozor et al, 2010;Gedefaw et al, 2018;Legesse et al, 2013;Mabe et al, 2014;Mengistu and Haji, 2015;Serkalem et al, 2014;Alemayehu and Bewket, 2017;Mekuyie et al, 2018;Belay et al, 2017;Chingala et al, 2017;Feleke et al, 2016;Kgosikoma et al, 2018;Opiyo et al, 2016;Yila and Resurreccion, 2013;Zampaligré et al, 2014). However, these research findings are fragmented and are not in a position to support policymakers in formulating context-specific strategies.…”
mentioning
confidence: 99%
“…Studies in different parts of the world revealed that climate change adaptation is taking place in dynamic biophysical, socioeconomic and political contexts, which fluctuate across time and location (Bawakyillenuo et al, 2016). Farmers' capacity to adapt with climate change effects is therefore a function of demographic, socioeconomic, institutional features of the households (Osumanu et al, 2017). However, the current study was reviewed literatures that were merely directed to semiarid agro-pastoral systems, which are very similar to the study area.…”
Section: Empirical Studies and The Conceptual Frameworkmentioning
confidence: 98%
“…Demographic features such as being male, educational status, farming experience and climate change perception of the household head were assumed to have a positive effect on adaptation decision (Temesgen et al, 2014). Likewise, socioeconomic structures of households such as farm income and total livestock in tropical livestock unit (TLU) were hypothesized to influence farmers' adaptation decision positively (Osumanu et al, 2017).…”
Section: Empirical Studies and The Conceptual Frameworkmentioning
confidence: 99%
“…Second, farmers will then scrutinize the available options, with the goal to identify what and why (adaptation measures) to adopt or implement. It must however be noted that many factors such as age, farming experiences, information, economic resources, education and institutions determines the adaptive capacity of households (Bawakyillenuo et al., 2016; Osumanu et al., 2017). The choice or decision to implement adaptation measures (adopt innovations) more often depends of the accessibility of adequate information, education, institutional support and asset base of vulnerable households (Bawakyillenuo et al., 2016).…”
Section: Theorymentioning
confidence: 99%